Dabartinių baltų bendrinių kalbų balsių spektrai - Kaukėnienė, Lidija (Baltistica, 2004)
THE SPECTRA OF ISOLATED VOWELS OF THE STANDARD BALTIC LANGUAGESThe article examines the spectra of isolated vowels of the standard Baltic languages, their acoustic, articulation features and their relationship with D. Jones’ cardinal vowels.The acoustic features of the separate vowels of Lithuanian and Latvian are not the same. The vowels [aˑ], [a], [i], [e̤ˑ], [u] are not pronounced in the same place. The timbre of Latvian [i], [e̤ˑ] is higher than that of similar vowels in Lithuanian, but the timbre of isolated Lithuanian [eˑ] is higher than that of the similar Latvian vowel. The timbre of the Latvian isolated vowels [aˑ], [a], [ɔ], [uˑ], [u] is lower than that of similar Lithuanian vowels. The Latvian isolated vowels [iˑ], [uˑ] have a higher F1, that is, they are more open than the corresponding Lithuanian vowels.Besides Latvian isolated [i], [e̤ˑ], [uˑ] are more tense and [u], [ɔ] are more rounded than similar Lithuanian vowels but Lithuanian [iˑ] is more tense than its Latvian correspondent.The spectral analysis and acoustic data allow us to claim that the isolated vowels of the standard Baltic languages are similar to the secondary and primary cardinal vowels. The marked extreme articulation is typical of Latvian and Lithuanian [oˑ], [ɔ], [iˑ], [uˑ].
Keywords: baltų kalbos; bendrinė kalba; balsiai